2011
DOI: 10.1097/ncn.0b013e3181f9db63
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Mediated Support for Adolescents With Cerebral Palsy or Spina Bifida

Abstract: Social support plays a key role in improving health outcomes for children with chronic conditions. Internet connections are an important component of adolescents' social networks and may overcome geographic and environmental barriers for those with disabilities. This article focuses on the processes associated with a 6-month online support intervention for adolescents with cerebral palsy or spina bifida. Specifically, the purpose was to determine the extent to which adolescents used an online peer support inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
88
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(96 citation statements)
references
References 20 publications
3
88
0
5
Order By: Relevance
“…Today's young people use the Internet via their smart phones, tablets or computers ubiquitously for social networking, leisure and recreation and for information gathering (ACMA 2009a;ACMA 2009b;Barnfather et al 2011). Almost all Australian teenagers regularly use social networking (90% of 12-17 year olds in 2009: ACMA 2009b).…”
Section: 'They Think I'm Really Cool and Nice'mentioning
confidence: 99%
See 1 more Smart Citation
“…Today's young people use the Internet via their smart phones, tablets or computers ubiquitously for social networking, leisure and recreation and for information gathering (ACMA 2009a;ACMA 2009b;Barnfather et al 2011). Almost all Australian teenagers regularly use social networking (90% of 12-17 year olds in 2009: ACMA 2009b).…”
Section: 'They Think I'm Really Cool and Nice'mentioning
confidence: 99%
“…The Internet could provide an opportunity for asynchronous communication without prejudice and time pressure (Barnfather et al 2011;Lewis 2010;Raghavendra et al 2012b). The young adults with disabilities in Cooper et al's study (2009) highlighted the importance of Internet technologies in developing friendships and reducing feelings of loneliness.…”
Section: 'They Think I'm Really Cool and Nice'mentioning
confidence: 99%
“…The development of a computermediated support and social groups for children with ESRD and other chronic conditions, for example the construction of an online social network which can be tested such as that described by Barnfather, et al (2011) andStewart, et al (2011) could be highly beneficial to the children.…”
Section: Implications For Health Care Practices and Policymentioning
confidence: 99%
“…The current research sought to explore how being online may address social participation factors by offering opportunities to build, enrich and maintain social ties and relationships beyond the confines of temporal, spatial and physical challenges [8,50,51]. Kirk noted many people with physical disabilities find it difficult to keep in touch with acquaintances as they move through life and points of transition can mean the end of valued relationships [52].…”
mentioning
confidence: 99%
“…Grace et al [7] found training young people who use AAC to use the Internet and social media increased opportunities for social participation. All young people, including those who use AAC, strive to establish intimate friendships and access emotional support during adolescence [37,[48][49][50].…”
mentioning
confidence: 99%